Strategi Pembelajaran Kooperatif dalam Pembelajaran PAI di MAN 2 Pasaman Barat - Ahmad Zainiansyah; Husnul Khotimah; Gusmaneli Gusmaneli (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Education is a forum for acquiring knowledge transferred from teachers to students. In education, the term model Learning can never be separated from every activity between teachers and teacher students where the learning model is a strategy in implementing educational activities. Dissatisfaction with the results of the learning model Conventional education makes education experts continue to strive for develop a learning model that is expected to be able to provide improvements in the implementation of the educational process. Wrong One learning model that is recommended is the learning model Cooperative This model emphasizes that students are able to learn to understand knowledge and learning work together to achieve certain learning goals. Cooperative learning also teaches students to interact and communicate well between fellow students. Learn to create Good relationships between students will train students to get used to it create good relationships between people. This goal is very appropriate with Islamic religious teachings. So with the existence of a learning model This cooperative, students will be able to have good interactions among humans both in the educational environment at school and in the community environment.